Microplastics in sea-surface waters surrounding Sweden sampled by manta trawl and in-situ pump. (April 2020) - Schönlau, Christine; Karlsson, Therese M.; Rotander, Anna; Nilsson, Helena; Engwall, Magnus; van Bavel, Bert; Kärrman, Anna
Abstract: Microplastics were sampled in open surface waters by using a manta trawl and an in-situ filtering pump. A total of 24 trawl samples and 11 pump samples were taken at 12 locations around Sweden. Overall, the concentration of microplastic particles was higher in pump samples compared to trawl samples. The median microplastic particle concentration was 0.04 particles per m −3 for manta trawl samples and 0.10 particles per m −3 in pump samples taken with a mesh size of 0.3 mm. The highest concentrations were recorded on the west coast of Sweden. Fibers were found in all samples and were also more frequent in the pump samples. Even higher concentrations of fibers and particles were found on the 0.05 mm pump filters. Using near-infrared hyperspectral imaging the majority of the particles were identified as polyethylene followed by polypropylene. Highlights: Microplastics (>0.3 mm) were found in 88% of trawl samples and 91% of pump samples, fibers were observed in all samples. Near-infrared hyperspectral imaging identified most of the particles as polyethylene. Pump samples had notably higher concentrations of microplastics in 5 out of 11 locations. Higher concentrations of microplastics and fibers when using a smaller mesh size of 0.05 mm The highest concentrations were recorded by the pump on the Swedish west coast.